Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1055/s-0034-1389954
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Partially Prevents Diabetic Neuropathy in Rats

Abstract: Neuropathy is one of the most common complications of diabetes mellitus. Although the beneficial effects of good blood glucose control on diabetic neuropathy are known, this control cannot completely prevent the occurrence and progression of diabetic neuropathy. The aim of this study was to investigate whether ozone prevents diabetic neuropathy. 36 adult female Sprague-Dawley rats were randomly divided into 6 groups (n=6): control (C), ozone (O), diabetic (D), ozone-treated diabetic (DO), insulin-treated diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
(39 reference statements)
3
11
0
2
Order By: Relevance
“…Erken et al demonstrated that the medical ozone therapy given by rectal insufflation reduces TOS and OSI levels and partially prevents diabetic neuropathy in rats [29]. In line with this study, we noticed renoprotective effects by MOA as reflected by decrements in TOS and OSI levels.…”
Section: Discussionsupporting
confidence: 91%
“…Erken et al demonstrated that the medical ozone therapy given by rectal insufflation reduces TOS and OSI levels and partially prevents diabetic neuropathy in rats [29]. In line with this study, we noticed renoprotective effects by MOA as reflected by decrements in TOS and OSI levels.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of chronic limb ischemia, which is habitually comorbidity in type 2 diabetes has been shown to be reduced with ozone therapy (Bocci, ; Bocci et al, ). Moreover, ozone therapy partially prevented diabetic neuropathy in rats 4 weeks after induction of diabetes following a 15‐day exposure to ozone (1.1 mg/kg), through oxidant/antioxidant mechanisms (Erken et al, ).…”
Section: Ozone Therapy To Attenuate Oxidative Stress In Diabetesmentioning
confidence: 99%
“…Therefore, this study aimed to investigate the effectiveness of systemic O 3 treatment in an animal model for RA. Previous studies have shown that systemic O 3 administration could be used safely in some clinical conditions, such as diabetes mellitus and renal disorders, 18,19 but a literature review indicates that this study is the first to evaluate the effect of systemic O 3 on both clinical and histopathological findings in an animal model of RA.…”
Section: Discussionmentioning
confidence: 95%